x^{m}e^{-bx^{n}}[a,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^a x^m e^{-bx^n}dx=\frac{1}{nb^{\frac{m+1}{n}}}γ\left(\frac{m+1}{n},ba^n\right)\\
&(2)  \displaystyle\int_a^{\infty} x^m e^{-bx^n}dx=\frac{1}{nb^{\frac{m+1}{n}}}Γ\left(\frac{m+1}{n},ba^n\right)\\
&(3)  \displaystyle\int_0^{\infty} x^m e^{-bx^n}dx=\frac{1}{nb^{\frac{m+1}{n}}}Γ\left(\frac{m+1}{n}\right)\\
&(4)  \displaystyle\int_{-\infty}^{\infty} x^{2m}e^{-bx^{2n}}dx=\frac{1}{nb^{\frac{2m+1}{2n}}}Γ\left(\frac{2m+1}{2n}\right)\\
\end{alignat}ただし、全て \(a,b,n,m \gt 0\)








<証明>

\((1)(2)(3)\) は全て \(bx^n=t\) と置きます。\((bnx^{n-1}dx=dt)\)

\begin{alignat}{2}
(1)  \displaystyle\int_0^a x^m e^{-bx^n}dx&=\displaystyle\int_0^{ba^n} \left(\frac{t}{b}\right)^{\frac{m}{n}} e^{-t} \cdot \frac{1}{bn} \left(\frac{t}{b}\right)^{\frac{1}{n}-1}dt\\
&=\frac{1}{nb^{\frac{m+1}{n}}}\displaystyle\int_0^{ba^n} t^{\frac{m+1}{n}-1}e^{-t}dt=\frac{1}{nb^{\frac{m+1}{n}}}γ\left(\frac{m+1}{n},ba^n\right)
&\\
(2)  \displaystyle\int_a^{\infty} x^m e^{-bx^n}dx&=\displaystyle\int_{ba^n}^{\infty} \left(\frac{t}{b}\right)^{\frac{m}{n}} e^{-t} \cdot \frac{1}{bn} \left(\frac{t}{b}\right)^{\frac{1}{n}-1}dt\\
&=\frac{1}{nb^{\frac{m+1}{n}}}\displaystyle\int_{ba^n}^{\infty} t^{\frac{m+1}{n}-1}e^{-t}dt=\frac{1}{nb^{\frac{m+1}{n}}}Γ\left(\frac{m+1}{n},ba^n\right)\\
&\\
(3)  \displaystyle\int_0^{\infty} x^m e^{-bx^n}dx&=\displaystyle\int_0^{\infty} \left(\frac{t}{b}\right)^{\frac{m}{n}} e^{-t} \cdot \frac{1}{bn} \left(\frac{t}{b}\right)^{\frac{1}{n}-1}dt\\
&=\frac{1}{nb^{\frac{m+1}{n}}}\displaystyle\int_0^{\infty} t^{\frac{m+1}{n}-1}e^{-t}dt=\frac{1}{nb^{\frac{m+1}{n}}}Γ\left(\frac{m+1}{n}\right)\\
\end{alignat}







\((4)\) \(bx^{2n}=t\) と置きます。\((b \cdot 2nx^{2n-1}dx=dt)\)
\begin{alignat}{2}
\displaystyle\int_{-\infty}^{\infty} x^{2m}e^{-bx^{2n}}dx&=2\displaystyle\int_0^{\infty} x^{2m}e^{-bx^{2n}}dx\\
&=2 \displaystyle\int_0^{\infty} \left(\frac{t}{b}\right)^{\frac{m}{n}}e^{-t} \cdot \frac{1}{2nb} \left(\frac{t}{b}\right)^{\frac{1}{2n}-1}dt\\
&=\frac{1}{nb^{\frac{2m+1}{2n}}}\displaystyle\int_0^{\infty} t^{\frac{2m+1}{2n}-1}e^{-t}dt\\
&=\frac{1}{nb^{\frac{2m+1}{2n}}}Γ\left(\frac{2m+1}{2n}\right)
\end{alignat}以上より$$\displaystyle\int_{-\infty}^{\infty} x^{2m}e^{-bx^{2n}}dx=\frac{1}{nb^{\frac{2m+1}{2n}}}Γ\left(\frac{2m+1}{2n}\right)$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です